PREMARITAL SEXUAL BEHAVIOR AND FACTORS AFFECTING YOUTH MARRIAGE (REVIEW OF MBA COUPLES IN PONOROGO REGENCY) - Susanti, Sri (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
Premarital sexual behavior in adolescents is caused by high adolescent sex drive, which occurs in an environment that begins to be permissive and almost limitless. In the end, physically children can mature more quickly and mature, but psychologically, economically, religiously, socially, as well as other forms of independence are not necessarily able to build a new community called family, this case will lead to other social problems, namely the occurrence of unwanted pregnancy / unpreparedness of teenagers to form new families whose ends end in divorce, abortion crime, the risk of Sexually Transmitted Diseases, and other social behaviors. Most of these adolescents have early marriage because they are forced to, and because they are pregnant out of wedlock. This research is a descriptive study using a qualitative approach. Data sources are obtained through interviews with informants or resource persons for married couples in an accident (MBA). Data collection techniques in research using indepth interview and observation. Data validity using triangulation method, and data analysis techniques using interactive analysis, three components namely data reduction, data presentation and conclusion drawn in the form of interactions with the process of collecting data as a cycle process. Based on the results of this study, it is known that the dominant factor in young marriage in the working area of the sub-district Religious Affairs Office (KUA) in the district of Ponorogo is due to pregnancy out of wedlock (Marrige By an Accident), in addition to the necessity and willingness to feel mutual love, and the presence of parents in the working area of the sub-district Religious Affairs Office (KUA) in the district of Ponorogo, that girls do not need to have high education because in the end girls will only take care of their husbands and children at home